APLIKASI JAVA DAN MYSQL PADA SISTEM INFORMASI MINIMARKET - Sanjaya, David Robby; Yuniarto, Yuniarto (Vocational School Diponegoro University, 2013)
David Robby Sanjaya, Yuniarto, in paper java and mysql application at minimarket information system explain that an endless human needs combined by their daily activities, made a lot of people reluctant to do shopping at a traditional market. Minimarket or supermarket that finally became a way out for this problem, because it had a good management system for organized the items and the transactions. Regulation of items and money at minimarket or supermarket require a good software. There are a lot of programming language that can be used for create this software, one of that is Java programming language. Java in this information system be used for create an interface to user while Mysql be used to manage a databases. Java programming language, Mysql, Netbeans and iReport are tools that applied to this Minimarket information system. Keywords: Minimarket Information System, iReport, Java, Mysql, Netbeans.